Maslahah sebagai Sumber Hukum Islam ‎Menurut Najm al-Din Al-Tufy‎ - Iffah Muzammil (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2010)
Amidst the debates surrounding the legality of al-maslahah as a source of islamic law, Najm al-Din al-Tufy—a Hanbalite legal theorist emerged with his bold proposition. He stated that maslahah must be upheld, be it supported by textual references or otherwise simplu because maslahah is the ultimate goal of islamic law. Further, he asserted that if mu’amalah aspects are concerned, maslahah is the most suitable reference. As to worships the reference is the consensus and texts.The thought of al-Tufy was heavily influenced by political unfoldings of his time, when the Mongols had defeated muslims. According to al-Tufy this situation was because of over reliance of muslims to religious texts. The remedy is to free muslims from the reliance of the texts.Because of the his boldness, al-Tufy had to accpet fierce criticism from other muslim legal theoriests. Admittedly, there are smo loopholes in al-Tufy ‘s proposition among which is his inability to prove an instance of contradiction between nass/ijma’ and maslahah. In addition, unlike other legal theoriests, he did not make classification maslahah.